What Fuels Electric Vehicle Adoption? Analyzing Determinants of Adoption Intention and Willingness to Pay - Nadiyatus Shofi; Imam Salehudin (Eduvest - Journal of Universal Studies, 2025)
Electric vehicles (EV) adoption in Indonesia is still lagging, with current sales volumes far below the government's target, particularly for battery electric vehicles (BEVs). This research aims to uncover the diffusion of BEVs by analyzing factors that influence their acceptance through adoption intention and willingness to pay, using an integrated model of the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2), which incorporates perceived risk, environmental concerns, and government support. Data from 329 respondents in major Indonesian cities were analyzed using partial least squares structural equation modeling (PLS-SEM). The results indicate that effort expectancy, habit, perceived risk, environmental concerns, and government support have an impact on EV adoption intention. Additionally, performance expectancy, price value, and adoption intention were found to positively influence willingness to pay for EV. These findings confirm the applicability of some factors of UTAUT2, perceived risk, environmental concern, and willingness to pay in examining EVs adoption in Indonesia, contributing to the literature on technology adoption in the automotive sector. This study also discusses implications that offer valuable insights for stakeholders in the EV market, thereby helping to promote electric vehicle adoption in Indonesia.